$a = C \sec \theta$

$b = W \csc \theta$

$a + b = L$

$C \sec \theta + W \csc \theta = L$

$W = \dfrac{L - C \sec \theta}{\csc \theta}$

$W = \dfrac{L}{\csc \theta} - \dfrac{C \sec \theta}{\csc \theta}$

$W = L\sin \theta - \dfrac{C \sin \theta}{\cos \theta}$

$W = L\sin \theta - C \tan \theta$

$\dfrac{dW}{d\theta} = L\cos \theta - C \sec^2 \theta$

$L \cos \theta = C \sec^2 \theta$

$L \cos \theta = \dfrac{C}{\cos^2 \theta}$

$\cos^3 \theta = \dfrac{C}{L}$

$\cos \theta = \dfrac{C^{1/3}}{L^{1/3}}$

$W = L \sin \theta - C \tan \theta$

$W = L \left( \dfrac{\sqrt{L^{2/3} - C^{2/3}}}{L^{1/3}} \right) - C \left( \dfrac{\sqrt{L^{2/3} - C^{2/3}}}{C^{1/3}} \right)$

$W = L^{2/3}\sqrt{L^{2/3} - C^{2/3}} - C^{2/3}\sqrt{L^{2/3} - C^{2/3}}$

$W = \left(L^{2/3} - C^{2/3}\right)\sqrt{L^{2/3} - C^{2/3}}$

$W = \left(L^{2/3} - C^{2/3}\right)\left(L^{2/3} - C^{2/3}\right)^{1/2}$

$W = \left(L^{2/3} - C^{2/3}\right)^{3/2}$ *answer*

(You may check the answer of Problem 20 above by using this formula)